Efektifitas Penambahan Semen Pada Stabilitas Tanah Lokal Samarinda - Syahrul, Syahrul (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Soil stability is the mixing of soil with certain materials, in order to improve the mechanical properties of the soil in order to meet technical requirements, cement stability aims to reduce shrinkage properties and high soil plasticity so as to increase the bearing capacity of the soil. The laboratory test parameters include testing the physical properties of the soil and the mechanical properties of the soil using type I cement with variations in the cement content of 0%, 5%, 10% and 15%. The study was conducted to determine the effectiveness of the percentage addition of cement, laboratory tests stated the effectiveness of stabilizing the addition of cement was 10% with the results of the free compression test of 5.446 kg/cm2 on the unconditioned sample, and 4.76 kg/cm2 of the conditioned for 3 days, the test results CBR was 145.38% without conditioned, and conditioned for 3 days was 141.96%.